Public-Private Partnerships : Reference Guide Version 3 - World Bank (World Bank, Washington, DC, 2017)
A growing number of governments are interested in partnering with the private sector to provide public infrastructure assets and services. The PPP Reference Guide aims to assist them. The Guide tackles the following questions: What are public-private partnerships (PPPs), why and when to use them. What kind of policy, legal, and institutional framework is needed to ensure PPPs achieve their objectives efficiently and effectively. What is the process for developing and implementing a PPP project. The Guide provides the most relevant examples and resources on key PPP topics and helps readers navigate the substantial body of knowledge that has been generated across the world by governments, international development institutions, academia, and the private sector. It is not a toolkit or a step-by-step guidebook; nor does it cover the specifics of PPPs in any given country or sector. The third edition includes new subjects such as stakeholder communication and engagement, environmental and social studies and standards, and climate change. Additional relevant sections include municipal PPPs and private participation in fragile and conflict-affected states.